Is low FODMAP diet effective in children with irritable bowel syndrome? - Güzide Doğan; Sibel Yavuz; Hale Aslantas; Beyhan Cengiz Özyurt; Erhun Kasırga (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: There is growing evidence that suggests that consumption of fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAPs) may result in some symptoms in certain patients with irritable bowel syndrome (IBS). This study aims to evaluate the efficacy of a low FODMAP diet in children with IBS by comparing it with the standard diet. METHODS: Sixty children between the ages of 6 and 18 who were diagnosed with IBS according to Rome IV criteria were included in this study. Randomly selected patients were divided into two groups as 30 patients on a low FODMAP diet and 30 patients on a general protective standard diet for the gastrointestinal tract. Patients were evaluated at the beginning, second and fourth months of the study. The data of the patients were recorded in the demographic data form. Patients were asked to score abdominal pain using the Visual Analogue Scale (VAS). The clinical status of the patient was scored by the doctor using the Clinical Global Impression Improvement (CGI-I) scale. RESULTS: There were no significant differences between groups about age, sex and symptom duration. When the pre-diet VAS scores were compared, the two groups were similar. The mean decrease in VAS score after two months of diet was 3.80+-1.10 in the low FODMAP group and 2.03+-1.03 in the standard group and was statistically significant. Post-dietary CGI-I score evaluation was determined to be statistically significant between the two groups. The increase in VAS scores in the fourth month was 2.97+-1.10 points in the Low FODMAP group and 1.63+-0.71 in the standard group, and was statistically significant. CGI-I score after the diet at the 4th month was also statistically significant between the two groups. CONCLUSION: A low FODMAP diet seems to be more effective for symptom control in IBS when compared to standard dietary advice. Further studies are needed for the unknowns that will be used in clinical practice, such as how long the diet will be continued and how effective it will be in which GIS diseases.